Origen de los sismos sentidos en Costa Rica durante el año 2023 - Linkimer Abarca, Lepolt (2024)
The 153 earthquakes felt in Costa Rica during 2023 can be grouped into four categories according to their origin: faulting in the Caribbean and Panama upper plates, interplate seismogenic zones of the Cocos and Caribbean plates, internal deformation of the subducted Cocos plate, and faulting in the boundary between the Cocos and Nazca plates. The felt seismicity represents only ~3 % of the total of 4438 events located by the National Seismological Network (RSN) in 2023, which together are equivalent to the energy released by an earthquake of moment magnitude (Mw) 6.6. The earthquakes caused by shallow faulting occurred on faults of all types and geometries, while those caused by subduction were of the reverse type and those associated with the CocoNazca boundary were pure strike-slip. The focal mechanisms of the earthquakes due to internal deformation of the Cocos plate were oblique with normal or reverse components. The largest felt earthquakes in 2023 were four events of Mw 6.4-6.5 with epicenters in neighboring countries, so they were slightly perceived in Costa Rica. The maximum intensity observed in 2023 was VI, due to two earthquakes (Mw 5.5 and 5.2) caused by faulting in the overriding plates.